Study on stingless bee honey stability for toothpaste production - Nur Azwani, Nordin @ Radin (2017)
Meliponini, a family of stingless bees is formed of several different species such as Melipona, Scaptotrigona, and Trigona. The Trigona species was known as the ‘Kelulut’ in Malaysia which is very useful in medically and therapeutically. ‘Kelulut’ has many compositions that give many benefits to human health such as vitamins and minerals that act as energy sources for human body, rich in probiotic bacteria that promote the health of the immune system, rich in phenolic compounds and active non-peroxide activity for antibacterial activity. Another important component of stingless bee honey is propolis. A chemical component of propolis of stingless bee honey plays a major role in treating human diseases especially for teeth, because it can avoid the formation of dental plaque and caries. Therefore, the toothpaste made of stingless bee honey is formulated in order to study the stability of honey for toothpaste production. The toothpaste formulation were analyse by pH, viscosity, cleaning ability and foaming ability. During the evaluation studies all the formulations were found to have PH, good cleaning ability, good foaming ability and viscosity characteristics. Finding from this work is vital for preserving the content of stingless bee honey during toothpaste making and may improve the quality of product made of stingless bee honey in the future which in turn may be beneficial to commercialize the stingless bee honey.